Propagation of electromagnetic waves through microstructured polar materials - G. Gantzounis; N. Stefanou (Physical Review B, 2007)
The optical response of finite slabs of polar materials, containing two- and three-dimensional periodic structures of air cavities, is studied by means of accurate numerical calculations using the layer-multiple-scattering method. Our results reveal the existence of strong resonant modes, originating from the excitation of flat-surface and cavity phonon-polaritons, which may be useful in terahertz applications.